Length difference of multi‐walled carbon nanotubes generates differential cytotoxic responses. Issue 9 (4th January 2021) - Do, Nhuan Thi; Kim, Suho; Kwak, Minjeong; Lee, Tae Geol; Jo, Dong‐Gyu; Lee, Sang‐Won; Kim, Se‐Hwa
Abstract: Carbon nanotubes have recently been rated as an effective biomaterial owing to their functionalization ability. However, the safety of multi‐walled carbon nanotubes (MWCNTs) has yet to be clearly understood. To investigate how cells differentially react to minor geometric differences, we prepared well‐dispersed and stable long and short MWCNTs showing an approximately 100‐nm length difference in an in vitro system. Through an optimal combination of bovine serum albumin (BSA) and fetal bovine serum (FBS) biosurfactants and ultrasonication, we first confirmed that the MWCNTs were maintained without aggregation throughout the experiments. Internalized MWCNTs in human coronary artery smooth muscle cells were then quantified in a label‐free manner using coherent anti‐Stokes Raman scattering, followed by an analysis of their localization via two‐photon excitation fluorescence. Intracellular MWCNTs were found to primarily localize in mitochondria with abnormal morphologies. Mitochondrial dysfunction, which was found to result from early stages of oxidative stress that consequently lead to cell death, was then proved via decreasing mitochondrial membrane potentials, with short MWCNTs showing significantly greater cytotoxicity than long MWCNTs. Our results suggest that even small length differences of MWCNTs may lead to differential responses in cells. Abstract : Multi‐walled carbon nanotubes (MWCNTs) were stabilized in cell culture condition by combination of biosurfactants and ultrasonication. Small length difference (100 nm) of MWCNTs generated differential cytotoxic responses via mitochondrial dysfunction in human coronary artery smooth muscle cells.